2018
DOI: 10.1007/s00705-017-3701-x
|View full text |Cite
|
Sign up to set email alerts
|

The complete nucleotide sequence and genome organisation of a novel member of the family Betaflexiviridae from Actinidia chinensis

Abstract: We report the complete genome sequence of a novel virus, tentatively named “actinidia seed-borne latent virus” (ASbLV), isolated from Actinidia chinensis in Auckland, New Zealand. The complete genome of ASbLV is 8,192 nucleotides long, excluding the 3ʹ poly(A) tail, contains four open reading frames, and is most closely related to Caucasus prunus virus (56% nucleotide sequence identity), a member of the genus Prunevirus. Based on the demarcation criteria of the family Betaflexiviridae, ASbLV is a new member of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…The virus (Actinidia chlorotic ringspot-associated virus, AcCRaV), presents double-membrane bodies in infected tissues, and has a genome composed of RNA segments in negative polarity, so it covers the typical features of members in the genus Emaravirus . A final report from New Zealand [ 90 ] described the complete genome sequence of a novel virus, tentatively named Actinidia seed-borne latent virus (ASbLV). The virus was identified from Actinidia chinensis (a seedling in home garden), its genome contains four open reading frames, and is most closely related to CPrV (56% nt identity), a member of the genus Prunevirus in Betaflexiviridae .…”
Section: Application Of High-throughput Sequencing Technology To Dmentioning
confidence: 99%
“…The virus (Actinidia chlorotic ringspot-associated virus, AcCRaV), presents double-membrane bodies in infected tissues, and has a genome composed of RNA segments in negative polarity, so it covers the typical features of members in the genus Emaravirus . A final report from New Zealand [ 90 ] described the complete genome sequence of a novel virus, tentatively named Actinidia seed-borne latent virus (ASbLV). The virus was identified from Actinidia chinensis (a seedling in home garden), its genome contains four open reading frames, and is most closely related to CPrV (56% nt identity), a member of the genus Prunevirus in Betaflexiviridae .…”
Section: Application Of High-throughput Sequencing Technology To Dmentioning
confidence: 99%
“…The first virus naturally infecting kiwifruit was reported in 2003 (Clover et al , 2003) and only three kiwifruit viruses had been reported by 2010 (Clover et al , 2003; Chavan et al , 2009; 2013). Recent studies have shown that at least 17 viruses have been detected in natural infections of kiwifruit, including cucumber necrosis virus (CNV), radish mosaic virus (RMV), cherry leaf roll virus (CLRV), cucumber mosaic virus (CMV), citrus leaf blotch virus (CLBV), potato virus X (PVX), pelargonium zonate spot virus (PZSV), tomato necrotic spot associated virus (TNSaV), tomato zonate spot virus (TZSV), turnip vein clearing virus (TVCV), Actinidia virus A (AcVA), Actinidia virus B (AcVB), Actinidia virus X (AVX), Actinidia virus 1 (AcV‐1), Actinidia seed‐borne latent virus (ASbLV) and Actinidia chlorotic ringspot‐associated emaravirus (AcCRaV) (Pearson et al , 2011; Blouin et al , 2012; 2013; 2018; Chavan et al , 2012; 2013; James and Phelan, 2016; Wang et al , 2016; Zheng et al , 2017; Veerakone et al , 2018; Zhao et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…and Actinidia chlorotic ringspot-associated emaravirus (AcCRaV) (Pearson et al, 2011;Blouin et al, 2012;Chavan et al, 2012;James and Phelan, 2016;Wang et al, 2016;Zheng et al, 2017;Veerakone et al, 2018;Zhao et al, 2019).…”
mentioning
confidence: 99%
“…In 2003, New Zealand researchers discovered for the first time the symptoms of viral infection caused by Apple stem grooving virus in a number of kiwifruit seedlings imported from China [3]. Subsequently, sixteen kiwifruit viruses have been identified worldwide, including eight that are non-specific: Apple stem grooving virus, Actinidia virus X, Alfalfa mosaic virus, Cucumber necrosis virus, Cucumber mosaic virus, Ribgrass mosaic virus, Turnip vein clearing virus and Tomato necrotic spot associated virus [3][4][5][6], six specific kiwifruit viruses: Actinidia virus A, Actinidia virus B, Actinidia citrivirus, Actinidia virus 1, Actinidia chlorotic ringspot-associated virus and Actinidia seed-borne latent virus [7][8][9][10], and two pathogenic viruses (Cherry leaf roll virus and Pelargonium zonate spot virus) [4]. These known kiwifruit viruses belong to different families, including Betaflexiviridae, Bromoviridae, Virgaviridae, Tombusviridae, Bunyaviridae, Secoviridae, and Closteroviridae.…”
Section: Introductionmentioning
confidence: 99%